Parental relationship with children during COVID-19 lockdown in Punjab Pakistan - Ahmad Bilal; Saba Nawaz; Shakeela Altaf (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: The Western studies had reported a change in parent child relationship during COVID-19 lockdown. The present study was conducted to assess the parental relationship with children during COVID-19 lockdown in Punjab province of Pakistan. METHODOLOGY: The study involved correlational research design. 529 parents from the Punjab province were recruited using a Google Form based questionnaire, which also contained information about the nature of the study and informed consent. The study was conducted from March 2020 to May 2020. The study was duly approved by Research Ethics Committee at The Islamia University of Bahawalpur vide No. REC/B/G-3/2020-S. The participants were required to give their consent for participation in the online study. The Child Parent Relationship Scale (CPRS) was appended to a single questionnaire to collect the data. The Statistical Package for the Social Sciences, version 25, was used for statistical analysis. The correlation analysis, t-test, and analysis of variance were used to compute results. RESULTS: The study found a statistically significant positive correlation between closeness and dependence and a positive significant but weak correlation of conflict with both closeness and dependence. The mothers had more closeness and dependence with their children as compared to fathers. There were found no age wise differences in a parental relationship for conflicts, closeness, and dependence. CONCLUSION: The study concluded that mothers had more closeness and dependence with their children as compared to fathers. Moreover, the age of parents had no effect on their relationship with children.